Pengaruh Kemandirian Belajar terhadap Kemampuan Penalaran Matematis Siswa SMP - Indah Mutiara Cahya; Kiki Nia Sania Effendi; Lessa Roesdiana (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to examine whether there is an effect of independent learning on the mathematical reasoning abilities of junior high school students. This research is a quantitative study with a correlational method. The population in this study were all class VIII students at one of the public schools in Karawang Regency for the 2019/2020 academic year with 1 class being selected as the research sample, namely class VIII C. Data collection techniques were obtained using tests in the form of a description of questions regarding reasoning abilities mathematics, and non-tests in the form of independent learning questionnaires, as well as interviews conducted online. Then, the data obtained were analyzed using a simple linear regression test. Based on the results of data processing, the regression equation is obtained, namely Y = 7.50 + 0.35X with a determination coefficient of 79%. Thus, independent learning has a positive influence on the variable mathematical reasoning ability of students by 79%, and 21% is influenced by other factors that are not included in this simple linear regression analysis. Furthermore, obtained a significance value of 0.00 less than 0.05, then H0 is rejected. Thus, it can be interpreted that there is a significant influence between independent learning on the mathematical reasoning abilities of junior high school students.